The psychological impact of quarantine on patients with COVID-19 at the lockdown center of Monastir (Tunisia) - Amjed Ben Haouala; Lina Brahmi; Sarra Ibn Khedher; Ahmed Mhalla; Ferid Zaafrane; Lotfi Gaha; Chawki Lousaief; Badii Amamou (Elsevier, 2024)
The COVID-19 pandemic has caused an unpredicted health crisis. Patients with covid-19 staying at a lockdown center are exposed to major psychological distress and need appropriate care. In our study, we were interested in COVID-19 patients, staying at a Tunisian lockdown center to evaluate the psychological repercussions of getting infected by COVID-19 and being placed in quarantine.Data collected was about the socio-demographic and clinical characteristics of the patients. Psychological distress was assessed by the 21-item Depression, Anxiety and Stress Scale (DASS-21)))in the Arabic version. Qualitative variables were described using frequencies and quantitative ones were described using means and standard deviations (DS).A comparison of sociodemographic variables between COVID-19 patients was performed through a T-test and one away ANOVA.Multivariate linear regression analyses were used to identify the variables independently associated with the DASS-21 score.A total of 148 patients were recruited. The mean age was 41.39, and the sex ratio was 1.17. The stay in the lockdown center was 35.86 days with extremes ranging from 7 to 86 days.79.7 % of participants were asymptomatic while 20.3 % of them were symptomatic. According to DASS-21 scores, 74.3 % of participants were not depressed and 64.9 % among them were not anxious. In addition, mild to moderate types of depression, anxiety and stress were more frequent than severe and extremely severe types. Several factors were significantly associated with psychological distress like the misjudgment of physical and mental health and the fear of being contagious. The female gender and the length of stay in the lockdown center were significantly associated with anxiety and depression. Age over 41 years old, physical illnesses, and symptoms of COVID-19 were significantly associated with the severity of psychological distress.The COVID-19 pandemic has created an unpredictable global crisis that is far from being a simple health crisis with repercussions on all dimensions of life. It had negatively impacted the economy, environment, social interactions, cultural life, and our physical health and mental health. Thus, multidisciplinary interventions after the period of infection are strongly recommended. Abstract: La pandémie du COVID-19 a provoqué une crise sanitaire imprévue. Les patients atteints de covid-19 séjournant dans un centre de confinement sont exposés à une détresse psychologique majeure et ont besoin de soins appropriés. Dans notre étude, nous nous sommes intéressés aux patients COVID-19, séjournant dans un centre de confinement tunisien pour évaluer les répercussions psychologiques d'être infectés par COVID-19 et d'être placé en quarantaine.Les données recueillies portaient sur les caractéristiques sociodémographiques et cliniques des patients. La détresse psychologique a été évaluée par l'échelle de dépression, d'anxiété et de stress (DASS-21) de 21 items) dans la version arabe. Les variables qualitatives ont été décrites à l'aide de fréquences et les variables quantitatives ont été décrites à l'aide de moyennes et d'écarts-types (DS).Une comparaison des variables sociodémographiques entre les patients atteints de COVID-19 a été réalisée au moyen d'un test T et ANOVA.Des analyses de régression linéaire multivariée ont été utilisées pour identifier les variables associées indépendamment au score DASS-21.Un total de 148 patients a été recrutés. L'âge moyen était de 41,39 ans et le rapport de masculinité était de 1,17. La durée du séjour dans le centre de confinement était de 35,86 jours avec des extrêmes allant de 7 à 86 jours.79,7 % des participants étaient asymptomatiques tandis que 20,3 % d'entre eux étaient symptomatiques. Selon les scores DASS-21, 74,3 % des participants n'étaient pas déprimés et 64,9 % d'entre eux n'étaient pas anxieux. De plus, les types légers à modérés de dépression, d'anxiété et de stress étaient plus fréquents que les types graves et extrêmement graves. Plusieurs facteurs étaient significativement associés à la détresse psychologique comme l'erreur de jugement de la santé physique et mentale et la peur d'être contagieux. Le sexe féminin et la durée du séjour dans le centre de confinement étaient significativement associés à l'anxiété et à la dépression. L'âge de plus de 41 ans, les maladies physiques et les symptômes de la COVID-19 étaient significativement associés à la gravité de la détresse psychologique.La pandémie de COVID-19 a créé une crise mondiale imprévisible qui est loin d'être une simple crise sanitaire avec des répercussions sur toutes les dimensions de la vie. Elle a eu des répercussions négatives sur l'économie, l'environnement, les interactions sociales, la vie culturelle, notre santé physique et notre santé mentale. Ainsi, des interventions multidisciplinaires après la période d'infection sont fortement recommandées.